2006
DOI: 10.1371/journal.pctr.0010010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Folic Acid and Betaine Supplementation on Flow-Mediated Dilation: A Randomized, Controlled Study in Healthy Volunteers

Abstract: Objectives:We investigated whether lowering of fasting homocysteine concentrations, either with folic acid or with betaine supplementation, differentially affects vascular function, a surrogate marker for risk of cardiovascular disease, in healthy volunteers. As yet, it remains uncertain whether a high concentration of homocysteine itself or whether a low folate status—its main determinant—is involved in the pathogenesis of cardiovascular disease. To shed light on this issue, we performed this study.Design:Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 58 publications
3
26
0
1
Order By: Relevance
“…Power calculations show that for the sample size and MZ/DZ ratio used here we should have had sufficient power to detect heritability as low as 45% and ample power to detect mean tHcy changes in line with those published in the literature (e.g. Olthof et al [27]). Nevertheless, our results need to be replicated using an independent cohort of North Europeans.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Power calculations show that for the sample size and MZ/DZ ratio used here we should have had sufficient power to detect heritability as low as 45% and ample power to detect mean tHcy changes in line with those published in the literature (e.g. Olthof et al [27]). Nevertheless, our results need to be replicated using an independent cohort of North Europeans.…”
Section: Discussionsupporting
confidence: 69%
“…Hyperhomocysteinemia – elevated tHcy levels – is recognised as a major risk factor for many common conditions, including cardiovascular disease, atherosclerotic and thromboembolic disease as well as for cognitive impairment [22,23,24]. Supplementation with folic acid has been shown to significantly reduce the levels of Hcy and hence in principle reduce the risk and incidence of theses conditions in the general population, as reported by Mayer et al [25], Wald et al [26], Olthof et al [27] and references therein. Several small-scale studies have previously investigated the role of the C677T functional variant at MTHFR in affecting response to folate supplementation [28,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Although 17 potentially relevant studies were identified and screened, 12 trials did not meet the eligibility criteria for the meta-analysis. Major reasons for exclusion of studies were as follows: not being randomized placebo-controlled trials (5 trials), utilization of patient populations with serious diseases such as chronic renal failure and steatohepatitis (4 trials), absence of data to calculate the net mean change in plasma homocysteine (2 trials), and involvement of methionine loading (1 trial).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…8 Studies in healthy volunteers show that 6 g/d of betaine lowers plasma homocysteine concentrations by 5% to 20%. [9][10][11][12][13][14][15][16][17][18][19][20] The purpose of this study was to perform a meta-analysis of randomized placebo-controlled trials that used daily betaine supplementation to identify the range in betaine's effects on lowering homocysteine.…”
Section: Introductionmentioning
confidence: 99%
“…Young women with hyperhomocysteinemia may be prone not only to systemic endothelial dysfunction but also placental endovasculature dysfunction 102 . Folic acid supplementation can substantially lower blood homocysteine levels in healthy subjects and patients with kidney disease [136][137][138][139] .…”
Section: Folic Acid Reduces Plasma Homocysteinementioning
confidence: 99%